(تطبيقات المبادئ الشرعية في المؤسسات المصرفية (دراسة حالة عن بيع العينة في بنك رعية الماليزي - Abdul Halim Harun
The Bay al-Inah concept is use in one of the available loan products in Islamic banking practiced by several financial institutions in Malaysia. Bay al-Inah from the Syari’ah perspective and within banking context means sales and purchases to obtain immediate cash facility. However, the status of this scheme is still questionable between pro and contra opinions of the traditional as well as modern religious specialists (‘ulama). In this research, the writer tries to establish a compromising approach and also to establish the extend of its application and usage as permitted by the Syari’ah principle in general: The writer obtains data from literature reviews, field observations, interviews and documents available. The writer focuses his research with Bank Rakyat Malaysia Berhad (BRMB) in Kuala Lumpur because Bank Rakyat Malaysia is the pioneer in offering this product to the market. The results indicate that this product is suitable to be used in Islamic capital markets in Malaysia in general and very specific in Bank Rakyat Malaysia Berhad (BRMB). BRMB has ensured to always updated all practices which may not be in line with the Syari’ah equipment e.g. the change of transaction instrument from gharar values to share certificate which nominal fixed values. However, this does not mean that BRMB has perfected the scheme as the writer has found that certain aspect and terms which are not really in line with principles of Islamic Syari’ah. The writer also tries to put forward several proposal and views as considerations and references for future updating prudent development of Islamic Banking in Malaysia in particular and the Islamic world in general.